KEPEMIMPINAN – “MODEL THE WAY” INSPIRASI BAGI TERWUJUDNYA BUDAYA RISIKO PERUSAHAAN: STUDI KASUS PADA PT. TELEKOMUNIKASI INDONESIA (Persero) Tbk - Tanto Kurnia (Center for Economic Studies Universitas Katolik Parahyangan, 2017)
Risk is the impact due to the uncertainty arising from the effort to achieve the company's goals. Risk management is a process to reduce corporate losses due to risk. PT Telkom one of the SOEs that has implemented risk management with COSO-CRM as references that combine with good corporate governance, has managed the risks, such as; legal and compliance. This success is due to the commitment of PT Telkom's leaders to make risk management as a corporate culture. Leaders who implemented leadership -